Peran Strategis IPNU dalam Membangun Karakter Generasi Muda - Siregar, Farhan; Hasibuan, Fathi Farich; Ashwarina, Najwa; Siregar, Rowina Anggian Putri; Astuti, Rahayu Fuji (At-Tadris: Journal of Islamic Education, 2025)
The Nahdlatul Ulama Student Association (IPNU) plays a strategic role in shaping the character of the younger generation through non-formal education that focuses on religious, moral and national values. Through cadre formation programs, leadership training and social skills development, IPNU instills noble moral values, discipline and a sense of nationalism. This research uses a phenomenological approach with descriptive qualitative methods to explore the experiences of IPNU members. The findings show that although IPNU has a positive impact, challenges such as limited resources and the influence of modern culture are the main obstacles. With an inclusive and adaptive strategy, IPNU is expected to continue to contribute to building youth character with integrity, morals and competence. This research aims to examine IPNU's strategic role in building the character of the younger generation through the various programs and activities it implements. Apart from that, this research will also look at the challenges faced by IPNU in carrying out this role amidst continuously developing social, political and technological dynamics.